Efektivitas Pelaksanaan Supervisi Manajerial sebagai Upaya Meningkatkan Kinerja Organisasi Guru Madrasah Aliyah: Efektivitas Pelaksanaan Supervisi Manajerial sebagai Upaya Meningkatkan Kinerja Organisasi Guru Madrasah Aliyah - Anis Choirun Niswah (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2025)
The effectiveness of madrasah supervision activities is an activity that needs to be carried out to see and evaluate the performance of an educational organization. Managerial supervision in its implementation still does not have a significant effect in improving the performance of educational organizations due to several obstacles. Therefore, researchers are interested in researching the implementation of managerial supervision in educational units and the influence of managerial supervision as a tool to improve the performance of educational organizations so that later learning activities can run as expected. This article was written using a literature review method through various sources to obtain data and information. The sources studied in preparing this scientific article were books, journals and articles on several online websites. The aim of writing this article is to carry out a case study and provide understanding to educational supervisors regarding managerial supervision in improving the organizational performance of teachers at Madrasah Aliyah. In conclusion, the implementation of managerial supervision at Madrasah Aliyah has an important influence, especially in terms of improving the performance of educational organizations and there are several ways that can be done to increase the effectiveness of the implementation of managerial supervision at Madrasah Aliyah.